RELATIONSHIP BETWEEN CLINICAL AND PATHOLOGIC FINDINGS IN PATIENTS WITH CHRONIC LIVER DISEASES: Clinical and Pathological findings in CLD Patients - Niazi, Maj Khalid Hamid Khan; Mirza, Shakeel Ahmad (Pakistan Armed Forces Medical Journal, 2010)
Objective: To explore the relationship between clinical findings of patients with chronic liver diseases and the pathologic grading and staging of liver tissues.Study Design: Non interventional comparative cross sectional study.Place and Duration of study: The study was conducted in Military Hospital (MH) Rawalpindi for duration of 06 months.Methods: The inflammatory activity and fibrosis of consecutive liver biopsies from 100 patients were determined according to the diagnostic criteria of chronic hepatitis. A comparative analysis was carried out for 100 patients with chronic liver diseases by comparing their clinical manifestations with the grading and staging of liver tissues.Results: It was revealed that age, index of clinical symptoms and physical signs were obviously relevant to the pathologic grading and staging of liver tissues (P